[REVIEW]: Rafał Kubicki, Prusy krzyżackie. Gospodarka i kultura na obszarach wiejskich, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2024, pp. 294. - Biskup, Radosław (Acta Mediaevalia. Series Nova, 2024)
The latest monograph by Rafał Kubicki, a medievalist from Gdańsk, is devoted - generally speaking - to rural areas in the state of the Teutonic Order. In this synthetic approach, the author draws on a rich tradition of research into the development of settlements, rural society, production relations and the organisation of agriculture, breeding and cultivation etc. in the territory in question. It is worth adding that this is not his first research expedition to the Prussian countryside under rule of Teutonic Order: in 2012 his habilitation on milling in the Teutonic Order’s state from the 13th to the mid-15th century was published. Similar topics are also taken up by Rafał Kubicki’s students: in 2022, at the University of Gdańsk, a dissertation was defended entitled "Komturstwo Tucholskie (1330-1454). Space-economy-society’, written by Grzegorz Woliński. [...]